THE IMPACT OF AI GAMIFIED TEACHING WITH LEARNING ENGAGEMENT AS THE MEDIATOR IN ORAL ENGLISH LANGUAGE ACHIEVEMENT, CHINA - Wang , YanXuanDing; Lee , Keok Cheong (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study aims to explore the impact of AI gamified teaching on oral English proficiency through learning engagement compared with traditional teaching methods in the Chinese context. In traditional English teaching, the conventional classroom model often leads to insufficient motivation for oral output and practice among learners. However, AI gamified teaching, which integrates intelligent interaction and game elements such as virtual scenarios and adaptive tasks, is believed to enhance oral proficiency by improving learning engagement through elements like task challenges and immediate feedback. The study analyzed the effects of intelligent feedback and immersive experiences in AI gamified teaching on learners’ behavioral engagement (such as frequent dialogue practice), emotional engagement (such as pleasure), and cognitive engagement (such as strategic language use), and examined the mediating effect of learning engagement and the response differences among learners of different levels. It is expected that AI gamified teaching can optimize oral teaching effectiveness by enhancing multi-dimensional engagement, with the mediating effect of emotional engagement possibly being the most significant. Learners at a lower level may show a more significant increase in learning engagement under personalized guidance. This study hopes to confirm that AI gamified teaching can enhance learning engagement through the synergy of intelligent technology and game mechanisms, thereby providing references for teaching practice. It is suggested that teachers combine adaptive tasks and social competition designs and provide more personalized emotional support for students with low proficiency in English.